(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigates the effect of drying on the nutritional and anti-nutritional composition of sweet and bitter cassava (Manihot esculenta). Using standard AOAC methods, four sample types—sweet and bitter cassava in both fresh and dried forms—were analyzed for proximate composition, mineral content, and anti-nutritional factors. The results showed that drying significantly (p < 0.05) reduced moisture (by 69.2% in sweet cassava and 67.4% in bitter cassava), hydrogen cyanide (by 34.9% in sweet cassava and 26.2% in bitter cassava), and oxalate levels (by 23.9% in sweet cassava and 20.6% in bitter cassava), while increasing carbohydrates (by 13.3% in sweet cassava and 14.9% in bitter cassava) and lipids (by 74.4% in sweet cassava and 72.6% in bitter cassava). The reduction in hydrogen cyanide and oxalate was more pronounced in the bitter variety. The reduction in hydrogen cyanide and oxalate was more pronounced in the bitter variety (p<0.05). The hydrogen cyanide reduces from 129.10 ± 6.00 Mg/100g, to 95.30 ± 6.10 Mg/100g and oxalate 79.43 ± 3.41 Mg/100g to 63.03 ± 2.14 Mg/100g in fresh and dried samples respectively. These findings emphasize the importance of drying as a processing method to enhance the safety and nutrient density of cassava consumed in Nigeria.